Influence of Manufacturing Faults on Squirrel Cage Induction Motor - Norry, Hayatullah; Yildiz, Ahmet; Aksun, Serhat; Aksoy, Cansu (Institute of Electrical and Electronics Engineers Inc., 2024)
Induction motors are the most widely used electric motors in the industry due to their robust structure and cost-effectiveness. Induction motors can be designed and produced from small to large powers. In addition to designing the induction motor in the correct and most appropriate way in terms of electrical and mechanical aspects, it is also important to design and produce each part in the correct dimensions. In general, the induction motor consists of a wound stator package, a cast rotor coupled with a shaft, two processed covers and a frame. In this study, the effects of production related issues such as faulty lamination, faulty stator package, faulty rotor package, faulty rotor casting, incorrect winding, and defective chip removal manufacturing on the electrical performance of the squirrel cage induction motor has been investigated. The problems that can be encountered in the production line of squirrel cage induction motors have been observed and discussed. © 2024 IEEE.
4th International Conference on Advances in Electrical, Computing, Communication and Sustainable Technologies, ICAECT 2024 -- 11 January 2024 through 12 January 2024 -- Bhilai -- 198331
Keywords: Induction motor; lamination; machining; manufacturing faults; rotor casting; winding